Impact of Economic Recession on Funding of Business Education Programmes in Nigerian Universities: A Case Study of University of Benin - Eshemogie, Kasimu Osigbeme; Brenda, Nick-Ezeh Uchenna (NIU Journal of Social Sciences, 2024)
Education in Nigeria has been plagued by inadequate funding over the years. This has continued despite various interventions by successive administrations. The current economic recession in the country has further worsened the situation with its attendant consequences on the different sectors of the economy, which includes the university education subsector. In order to capture the challenges of economic recession, this paper undertook a historical survey of global economic recession and Nigeria and the impact on funding education especially, the university education subsector programmes with specific reference to business education programme of the Department of Vocational and Technical Education, University of Benin. It analyzes the budgetary allocation to the department in the last four years and determines the adequacy of the allocation to business education programme, in the face of inflationary trend in the recessed economy. Findings show that business education programme has been inadequately funded and that there has been neglect of infrastructure and the provision of teaching and learning facilities. The survey also unraveled the fact that budget was not allocated to training of needed manpower, as focus was on payment of salaries and purchase of consumables for the day to day running of the department. Recommendations have been made amongst which are: the need to improve internally generated revenue through entrepreneurship centres and the need for government to increase the budgetary allocation to the education sector to meet the recurrent and capital expenditure for implementation of business education programmes. Keywords: Economic Recession, Business Education, Funding of Business Education Programmes, Nigerian Universities, University of Benin